Mudançasrecentes na fecundidade adolescente no Brasil: a associação com a escolaridade continua a mesma? - Paulo Henrique Viegas Martins (2016)
This study analyzes the behavior of fertility of women aged 15 to 19 years, named adolescents, according to groups of years of study. The main objective is to study the association between adolescent fertility and education in Brazil in the context of fertility changes of this age group. Specifically we seek: a) to analyze how and if the association between current fertility of adolescents and education changed between 1991 and 2010; b) to analyze how and if the association between parity of adolescents and education changed between 1991 and 2010. To conduct the study, we used the Census of 1991, 2000 and 2010. To estimate the odds of being a mother in adolescence we used a logistic regression model, whereas for analysis of parity used a Poisson model with zero inflated. The results suggest that even after the decline of fertility of adolescents between 2000 and 2010 and improving education in the same period, there was an increase in the odds of being a mother and repeat fecundity for adolescents with 4-8 years of study and decreases the same chances for those with 0-3 years of study. Finally, it was concluded that there was an increase of fertility differences according to education, when comparing adolescents with 4-8 years of study to those with 9 or more years of schooling. Thus, the results of this work suggest that the decline in adolescent fertility in Brazil between 2000 and 2010 should not be explained by the decrease in the risk of mother to schooling, but by changes in the educational composition of the country experienced in the first decade of this century.